KEWAJIBAN PERPAJAKAN PASCA PP 23/2018: SIAPKAH WAJIB PAJAK MELAKSANAKANNYA? - Dian Purnama Sari; Patricia Febrina Dwijayanti; Rwa Abimantrana Ksemadyastu; Michael Michael (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
This study is to empirically test the readiness of Corporate Taxpayers to carry out tax obligations after Government Regulation number 23/2018 (PP 23/2018). The survey method is an appropriate method for this research. Respondents as the object of this research are MSME owners in East Java, in the form of a CV and calculating Income Tax based on PP 23/2018. The results of this study indicate that tax socialization, taxpayer knowledge and tax sanctions have a positive effect on readiness to carry out tax liability after PP 23/2018. Interestingly, awareness of tax compliance does not affect the readiness of taxpayers to carry out their tax liability after PP 23/2018.